2018
DOI: 10.1111/bph.14490
|View full text |Cite
|
Sign up to set email alerts
|

The transient receptor potential melastatin 4 channel inhibitor 9‐phenanthrol modulates cardiac sodium channel

Abstract: Our results indicate that 9-phenanthrol modulates the gating properties of cardiac sodium channels and inhibits I and I , which may contribute to its antiarrhythmic and cardioprotective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…All reagents were purchased from Sigma unless otherwise indicated. Cells were patch-clamped using the whole-cell configuration as previously described 15, 16. For action potential recordings, patch pipettes (resistance 2 to 3 MΩ) were filled with pipette solution containing (in mM): 110 K-aspartate, 30 KCl, 5 NaCl, 0.1 EGTA,10 HEPES, 5 MgATP, 5 creatine phosphate, 0.05 cAMP, pH 7.2 with KOH.…”
Section: Methodsmentioning
confidence: 99%
“…All reagents were purchased from Sigma unless otherwise indicated. Cells were patch-clamped using the whole-cell configuration as previously described 15, 16. For action potential recordings, patch pipettes (resistance 2 to 3 MΩ) were filled with pipette solution containing (in mM): 110 K-aspartate, 30 KCl, 5 NaCl, 0.1 EGTA,10 HEPES, 5 MgATP, 5 creatine phosphate, 0.05 cAMP, pH 7.2 with KOH.…”
Section: Methodsmentioning
confidence: 99%
“…It can become important if increased under pathological conditions (Saint, 2006). The study by (Hou et al 2018) shows little effect of 9-Phen in normal tissue but large effects when the late Na + current is enhanced by ATXII or by overexpression in CHO cells. Conditions that enhance late INa + did not apply to our experiments.…”
Section: Study Limitationsmentioning
confidence: 99%
“…(Chen et al, 1993;Dosdall et al, 2008;Myles et al, 2012) and we observed no effects of Lugol's on heart rate or pressure development (Table 2). 9-Phen was reported, to target late Na + current in some pathologies (Hou et al, 2018).…”
Section: Study Limitationsmentioning
confidence: 99%
“…In either case, the cardiac action potentials (APs) were shortened suggesting a role of TRPM4 in the repolarization phase. However, discrepancies exist in these studies regarding their baseline cardiac phenotypes and doubts regarding the lack of specificity of 9-phenanthrol [21][22][23].…”
Section: Deletion Of Trpm4 Alters the Function And Expression Of Na Vmentioning
confidence: 99%